FEATURES OF COMPENSATION OF DAMAGES DAMAGED BY VEHICLES - Шуст, Наталія Борисівна; Зінченко, Марія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the work is to highlight the problematic issues that arise in practice during the compensation of damage caused by vehicles, and to develop proposals for ways to solve them, to analyze current Ukrainian legislation in the field of compensation for damage caused by vehicles. Research methods: general and special methods are used. Results: on the basis of the analysis of the case law and the current legislation of Ukraine, some problems of enforcement of certain rules of law have been identified. Accordingly, proposals for the optimization of Ukrainian civil law have been developed. Discussion: legislation, scientific positions of individual scientists. Together with scientific and technological development and trusted transport equipment, the number of road accidents has increased, and therefore the need and need for their needs is needed for all countries of the world, including Ukrainian. There is a tendency for a large number of offenses that do not reveal that they mark their participants in their own activities. The Constitution of Ukraine in Art. Art. 3, 27, 41, 68 enshrines the right to protect a person for the benefit of any school tomorrow. Also, issues related to schoolchildren, regulated in the Civil Code of Ukraine, concerning Art. 22, you mean that the person who caused damage in the achievement of his civilian person is entitled to his job. Lack of sufficient legal regulation, and a certain complexity of legal relationships are the reasons for the interest in the study and analysis of professional legal literature, regulatory framework, case law materials on compensation for damage caused by vehicles. There is a tendency for a large number of offenses that remain undisclosed, which in turn cause harm to participants. It should be noted that the main issue of compensation for damage caused by vehicles is insufficiently regulated in the legislation of Ukraine, which causes problematic issues in practice.